An investigation on the feasibility of fused deposition modelling process in EDM electrode manufacturing. (August 2019) - Equbal, Azhar; Equbal, Md. Israr; Sood, Anoop Kumar
Abstract: To satisfy the need for rapid and economical fabrication of EDM (Electrical discharge machining) electrode techniques of additive manufacturing are gaining more popularity. In the similar direction, the study presents an investigation on the feasibility of EDM electrode fabrication using FDM (Fused deposition modelling) process of additive manufacturing. Metallization of FDM parts were done to satisfy the conductivity requirement in EDM. To satisfy the thickness requirement of metalized FDM electrode, a thickness control method is also proposed. Suitability of fabricated electrode was tested by machining at different EDM settings and its performance was assessed by a comparative evaluation with a conventional solid copper electrode at the similar machining conditions. It was observed that performance of metalized FDM electrode was same as the performance of conventional solid copper electrode measured in terms of material removal rate ( MRR ), tool wear rate ( TWR ) and surface roughness ( Ra ). Machining performances of two electrodes are however different when measured in terms of dimensional accuracy. To enhance the machining performance of metalized FDM electrode pareto optimality approach was used. Pareto optimal solutions were obtained by a well-established multi-objective genetic algorithm (MOGA).